Case report: A novel mutation in the EYA1 gene in a child with branchiootic syndrome with secretory otitis media and bilateral vestibular hypofunction - He, Jun; Mahmoudi, Ahmad; Gu, Yu; Fu, Jinfeng; Yuan, Qiulin; Liu, Wei (Frontiers in Genetics, 2024)
Branchiootic syndrome (BOS) is a rare, autosomal dominant syndrome characterized by malformations of the ear associated with hearing loss, second branchial arch anomalies, and the absence of renal anomalies. Herein, we report the case of an 8-yearold male patient with BOS. The proband also experiences mixed conductive and sensorineural hearing loss in the right ear, and severe-to-profound sensorineural hearing loss in the left ear. Preauricular pits, branchial fistulae, and cochlear hypoplasia were present bilaterally. Type III cup-shaped ear, and external auditory canal stenosis were detected in the right ear. Lateral semicircular canal-vestibule dysplasia was detected in the left ear. Moreover, the patient had unilateral secretory otitis media (SOM) in the right ear and bilateral vestibular hypofunction (VH), which has not been reported in previous studies. The patient's hearing on the right side was restored to nearly normal after myringotomy. Whole exome sequencing identified a novel frameshift mutation in EYA1 (NM_000503.6): c.1697_1698delinT (p.(Lys566IlefsTer73)) in the proband, which was defined a "pathogenic" mutation according to American College of Medical Genetics and Genomics guidelines. This is the first report of a child presenting with BOS, SOM and VH, which expands the known clinical manifestations of this syndrome.We also observed a novel EYA1 gene mutation in this patient with BOS, which enriches the mutation map and provides a reference for genetic diagnosis of this syndrome.